Promoting dietary changes for achieving health and sustainability targets - Bellamy, Angelina Sanderson; Furness, Ella; Mills, Susanna; Clear, Adrian; Finnigan, Samantha Mitchell; Meador, Elliot; Milne, Alice E.; Sharp, Ryan T. (Frontiers in Sustainable Food Systems, 2023)
Globally, about 21–37% of total greenhouse gas (GHG) emissions are attributable to food systems. Dietary-related non-communicable diseases have increased significantly from 1990–2019 at a global scale. To achieve carbon emissions targets, increase resilience, and improve health there is a need to increase the sustainability of agricultural practises and change dietary habits. By considering these challenges together and focusing on a closer connection between consumers and sustainable production, we can benefit from a positive interaction between them. Using the 2019 EAT Lancet Commission dietary guidelines, this study analysed interview data and food diaries collected from members of Community Supported Agriculture (CSA) schemes and the wider UK population. By comparing the environmental sustainability and nutritional quality of their respective diets, we found that CSA members consumed diets closer to the EAT Lancet recommendations than controls. We identified significant differences in daily intakes of meat; dairy; vegetables; legumes; and sugar, and the diets of CSA members emitted on average 28% less CO2 compared to controls. We propose that agricultural and wider social and economic policies that increase the accessibility of CSAs for a more diverse demographic could support achieving health, biodiversity, and zero-emission policy targets.